RANCANG BANGUN PERTANIAN STROBERI BERBASIS INTERNET OF THINGS - I Komang Leo Puja Artana; Dewa Made Wiharta; Linawati Linawati (Jurnal SPEKTRUM, 2020)
Technological developments have been utilized in various fields of science, includingagriculture. Technology support in agriculture has been proven to be able to provide betterproduction results. In this study, an IoT-based agricultural environmental monitoring systemwas developed. The system was built using Raspberry Pi as a microcontroller and dataprocessing center, equipped with a moisture sensor and a DHT 11 temperature sensor. Thissystem was applied to a laboratory-scale strawberry farm. The system works automatically toregulate the temperature and humidity of the plant environment. If the temperature andhumidity of the strawberry plants do not meet the standards, the pump will automatically waterto keep the strawberry plants at the appropriate temperature and humidity. The system is alsoequipped with a notification feature so that strawberry farmers can obtain information throughtelegram media when the temperature of the strawberry plants is hot and the soil of thestrawberry plants is dry. This tool is also equipped with a webcam camera as an additionalfeature that serves to detect the level of ripeness of the strawberries in terms of the color of thefruit. The camera will detect the color of the strawberry, and if the strawberry is red, thestrawberry is categorized as ripe, and the farmer will get a notification via telegram in the formof a picture that the strawberry is ready to be harvested.